Accelerating productive energy access for the just transition among vulnerable communities; a case study of West Nile, Uganda - Amanubo, Amos (Department of Environmental and Geographical Science, 2024)
Sustainable enhancement of energy security has been considered crucial for a just transition towards low carbon sustainable socio-economic development including poverty eradication, job creation and decent employment, food security, among others. Nevertheless, multidimensional energy poverty is still a widespread phenomenon, profound in low-income economies such as Uganda, more so in the rural areas. To investigate the key issues underlying productive energy access and energy-livelihood interlinkages in the context of micro and small enterprises, this research carried out a case study survey of 129 enterprises in West Nile, Uganda, where previous studies mainly focused on household energy consumption. Data were analysed based on the Multidimensional Energy Poverty Indices (MEPI) framework, capturing how the 4A's dimensions of accessibility, availability, affordability and acceptability reinforce or constrain energy choices. The study found that most enterprises rely on grid (43%), then solar PV (16%) and lastly fuel generator (10%) to meet their energy needs, while 31% are energy bricoleurs who diversified their energy sources to guarantee energy security. The prevailing source of energy used is closely associated with socioeconomic enabling or disabling factors such as gender, education, business type, and market and finance based factors. Further, the results show that several enterprises experienced severe challenges in all dimensions of the 4A's framework, and strong interlinkages existed between energy access and the livelihoods of the enterprise owners. Policies and programmes that seek to address productive energy access should be multidimensional, and should consider gender, education and capacity building, and the key types of enterprises driving the local economy. The potential of solar PV should be reinforced using innovative financial mechanisms and product design to ensure it is both affordable and suited for the needs of the local businesses. Addressing productive energy access should be considered as one of the key strategies to promote sustainable livelihoods.